The Dardanelles Campaign in the Spanish Press - Mehmet Gündüz (Yakın Dönem Türkiye Araştırmaları)
The world press closely followed the developments on the Çanakkale Front due to its strategic importance. The Spanish press also conveyed the developments on this front to its readers. Although the Kingdom of Spain was a neutral country, a distinction existed between the Entente and the Alliance both in the Spanish public and the press. The political stances of newspapers and magazines were also reflected in the news about the Dardanelles Campaign. The Spanish press reported news about both the Entente and the Central Powers, but mostly used the news sources from the Entente states. The fact that the Spanish press watched the war through its own reporters rather than from foreign media sources coincided with a period when the Entente had withdrawn from the region. This study examines how the developments in the Çanakkale Front were reflected in the Spanish press and how the press approached these events. The article examines . This workwithin its scope the relevant period of the Spanish press. This study uses the document analysis method to examine the main issues regarding the reasons for the Dardanelles Campaign and its land and sea battles, as well as the plans the parties made to achieve success.